Comparison of Prenatal Health Management State and Educational Needs for Pregnant Women with Advanced Maternal Age and Under the Age of 35 - Hee Jung Wang; Hye Sook Park; Il Ok Kim (Korean Society of Women Health Nursing, 2013)
PURPOSE: This study was done to confirm prenatal health management and educational needs for pregnant women with advanced maternal age (AMA) and pregnant women under 35 years of age. METHODS: This study was a descriptive research in which self-report questionnaires were used. Participants were 279 pregnant women (83 AMA and 196 less than 35). RESULTS: Only 32.5% of AMA women had received prenatal education and 51.8% reported wanting internet education. AMA women, compared to the under 35 women, had higher levels of self-awareness of health problems and possibility of health problems but lower levels of alcohol experience before pregnancy. For prenatal health management, scores were low for prenatal exercise, prenatal education and nutrition. For prenatal health management education, AMA women reported high levels of need for education on health problems. CONCLUSION: The results indicate that prenatal health management education must be given considering differences in age-related requirements by emphasizing health care and obstetric complications during pregnancy for AMA womenand anemia and information on substance use during pregnancy for women under 35. Reliable internet-based education programs need to be developed using available information and communication technology for the increasing number of employed pregnant women.